<< Chapter < Page Chapter >> Page >

Solve ln ( x 3 ) 4 ln ( x ) = 1 .

x = 1 e

Got questions? Get instant answers now!

When evaluating a logarithmic function with a calculator, you may have noticed that the only options are log 10 or log, called the common logarithm , or ln , which is the natural logarithm. However, exponential functions and logarithm functions can be expressed in terms of any desired base b . If you need to use a calculator to evaluate an expression with a different base, you can apply the change-of-base formulas first. Using this change of base, we typically write a given exponential or logarithmic function in terms of the natural exponential and natural logarithmic functions.

Rule: change-of-base formulas

Let a > 0 , b > 0 , and a 1 , b 1 .

  1. a x = b x log b a for any real number x .
    If b = e , this equation reduces to a x = e x log e a = e x ln a .
  2. log a x = log b x log b a for any real number x > 0 .
    If b = e , this equation reduces to log a x = ln x ln a .


For the first change-of-base formula, we begin by making use of the power property of logarithmic functions. We know that for any base b > 0 , b 1 , log b ( a x ) = x log b a . Therefore,

b log b ( a x ) = b x log b a .

In addition, we know that b x and log b ( x ) are inverse functions. Therefore,

b log b ( a x ) = a x .

Combining these last two equalities, we conclude that a x = b x log b a .

To prove the second property, we show that

( log b a ) · ( log a x ) = log b x .

Let u = log b a , v = log a x , and w = log b x . We will show that u · v = w . By the definition of logarithmic functions, we know that b u = a , a v = x , and b w = x . From the previous equations, we see that

b u v = ( b u ) v = a v = x = b w .

Therefore, b u v = b w . Since exponential functions are one-to-one, we can conclude that u · v = w .

Changing bases

Use a calculating utility to evaluate log 3 7 with the change-of-base formula presented earlier.

Use the second equation with a = 3 and e = 3 :

log 3 7 = ln 7 ln 3 1.77124 .

Got questions? Get instant answers now!
Got questions? Get instant answers now!

Use the change-of-base formula and a calculating utility to evaluate log 4 6 .


Got questions? Get instant answers now!

Chapter opener: the richter scale for earthquakes

A photograph of an earthquake fault.
(credit: modification of work by Robb Hannawacker, NPS)

In 1935, Charles Richter developed a scale (now known as the Richter scale ) to measure the magnitude of an earthquake . The scale is a base-10 logarithmic scale, and it can be described as follows: Consider one earthquake with magnitude R 1 on the Richter scale and a second earthquake with magnitude R 2 on the Richter scale. Suppose R 1 > R 2 , which means the earthquake of magnitude R 1 is stronger, but how much stronger is it than the other earthquake? A way of measuring the intensity of an earthquake is by using a seismograph to measure the amplitude of the earthquake waves. If A 1 is the amplitude measured for the first earthquake and A 2 is the amplitude measured for the second earthquake, then the amplitudes and magnitudes of the two earthquakes satisfy the following equation:

R 1 R 2 = log 10 ( A 1 A 2 ) .

Consider an earthquake that measures 8 on the Richter scale and an earthquake that measures 7 on the Richter scale. Then,

8 7 = log 10 ( A 1 A 2 ) .


log 10 ( A 1 A 2 ) = 1 ,

which implies A 1 / A 2 = 10 or A 1 = 10 A 2 . Since A 1 is 10 times the size of A 2 , we say that the first earthquake is 10 times as intense as the second earthquake. On the other hand, if one earthquake measures 8 on the Richter scale and another measures 6, then the relative intensity of the two earthquakes satisfies the equation

log 10 ( A 1 A 2 ) = 8 6 = 2 .

Therefore, A 1 = 100 A 2 . That is, the first earthquake is 100 times more intense than the second earthquake.

How can we use logarithmic functions to compare the relative severity of the magnitude 9 earthquake in Japan in 2011 with the magnitude 7.3 earthquake in Haiti in 2010?

To compare the Japan and Haiti earthquakes, we can use an equation presented earlier:

9 7.3 = log 10 ( A 1 A 2 ) .

Therefore, A 1 / A 2 = 10 1.7 , and we conclude that the earthquake in Japan was approximately 50 times more intense than the earthquake in Haiti.

Got questions? Get instant answers now!
Got questions? Get instant answers now!

Questions & Answers

why n does not equal -1
K.kupar Reply
ask a complete question if you want a complete answer.
I agree with Andrew
f (x) = a is a function. It's a constant function.
Darnell Reply
proof the formula integration of udv=uv-integration of vdu.?
Bg Reply
Find derivative (2x^3+6xy-4y^2)^2
Rasheed Reply
no x=2 is not a function, as there is nothing that's changing.
Vivek Reply
are you sure sir? please make it sure and reply please. thanks a lot sir I'm grateful.
i mean can we replace the roles of x and y and call x=2 as function
if x =y and x = 800 what is y
Joys Reply
how do u factor the numerator?
Drew Reply
Nonsense, you factor numbers
You can factorize the numerator of an expression. What's the problem there? here's an example. f(x)=((x^2)-(y^2))/2 Then numerator is x squared minus y squared. It's factorized as (x+y)(x-y). so the overall function becomes : ((x+y)(x-y))/2
The problem is the question, is not a problem where it is, but what it is
I think you should first know the basics man: PS
Yes, what factorization is
Antonio bro is x=2 a function?
Yes, and no.... Its a function if for every x, y=2.... If not is a single value constant
you could define it as a constant function if you wanted where a function of "y" defines x f(y) = 2 no real use to doing that though
Why y, if domain its usually defined as x, bro, so you creates confusion
Its f(x) =y=2 for every x
Yes but he said could you put x = 2 as a function you put y = 2 as a function
F(y) in this case is not a function since for every value of y you have not a single point but many ones, so there is not f(y)
x = 2 defined as a function of f(y) = 2 says for every y x will equal 2 this silly creates a vertical line and is equivalent to saying x = 2 just in a function notation as the user above asked. you put f(x) = 2 this means for every x y is 2 this creates a horizontal line and is not equivalent
The said x=2 and that 2 is y
that 2 is not y, y is a variable 2 is a constant
So 2 is defined as f(x) =2
No y its constant =2
what variable does that function define
the function f(x) =2 takes every input of x within it's domain and gives 2 if for instance f:x -> y then for every x, y =2 giving a horizontal line this is NOT equivalent to the expression x = 2
Yes true, y=2 its a constant, so a line parallel to y axix as function of y
Sorry x=2
And you are right, but os not a function of x, its a function of y
As function of x is meaningless, is not a finction
yeah you mean what I said in my first post, smh
I mean (0xY) +x = 2 so y can be as you want, the result its 2 every time
OK you can call this "function" on a set {2}, but its a single value function, a constant
well as long as you got there eventually
volume between cone z=√(x^2+y^2) and plane z=2
Kranthi Reply
answer please?
It's an integral easy
V=1/3 h π (R^2+r2+ r*R(
How do we find the horizontal asymptote of a function using limits?
Lerato Reply
Easy lim f(x) x-->~ =c
solutions for combining functions
Amna Reply
what is a function? f(x)
Jeremy Reply
one that is one to one, one that passes the vertical line test
It's a law f() that to every point (x) on the Domain gives a single point in the codomain f(x)=y
is x=2 a function?
restate the problem. and I will look. ty
jon Reply
is x=2 a function?
What is limit
MaHeSh Reply
it's the value a function will take while approaching a particular value
don ger it
what is a limit?
it is the value the function approaches as the input approaches that value.
Its' complex a limit It's a metrical and topological natural question... approaching means nothing in math
is x=2 a function?
3y^2*y' + 2xy^3 + 3y^2y'x^2 = 0 sub in x = 2, and y = 1, isolate y'
Andrew Reply
what is implicit of y³+x²y³=5 at (2,1)
Estelita Reply
tel mi about a function. what is it?
A function it's a law, that for each value in the domaon associate a single one in the codomain
function is a something which another thing depends upon to take place. Example A son depends on his father. meaning here is the father is function of the son. let the father be y and the son be x. the we say F(X)=Y.
yes the son on his father
a function is equivalent to a machine. this machine makes x to create y. thus, y is dependent upon x to be produced. note x is an independent variable
x or y those not matter is just to represent.
Practice Key Terms 7

Get the best Calculus volume 1 course in your pocket!

Source:  OpenStax, Calculus volume 1. OpenStax CNX. Feb 05, 2016 Download for free at http://cnx.org/content/col11964/1.2
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Calculus volume 1' conversation and receive update notifications?